Analysis of Land Use And Cover and its Proportion for Ruminant Farming in Lima Puluh Kota Regency - Cori Qamara; Dwi Yuzaria; Fuad Madarisa; I Putu Gede Didik Widiarta (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2025)
The purpose of this study was to assess the potential for ruminant livestock development in Lima Puluh Kota District by analyzing land cover and land use. A high-accuracy land cover map (kappa = 0.97) was created using Landsat 8-9 Path/Row 127/060 satellite imagery and the Random Forest (RF) classification method. Analysis was conducted using Geographic Information System (GIS) processes to evaluate land suitability. Slope, elevation, and proximity to water sources. As a result, about 35% of the district is highly suitable (S1) for ruminant farming. Due to the abundance of natural fodder and conditions conducive to extensive grazing systems, these ideal areas are mostly zones of dryland agriculture, mixed gardens and shrubs. However, due to limited fodder supply and geographical constraints, densely forested environments and urban environments are categorized as moderately suitable or unsuitable. The importance of improving livestock spatial arrangements was highlighted by the significant mismatches found when existing livestock population data were spatially overlaid with suitability maps. In conclusion, Lima Puluh Kota District has a strong biophysical basis to support ruminant livestock development. However, to ensure sustainable and effective use of land resources for livestock, spatial planning and land use policies must be aligned.